Kepastian Hukum Akta Perubahan Badan Kredit Desa Menjadi PT. Lembaga Keuangan Mikro - Mohammad Reynaldy Adam; Wiwik Wulandari (Faculty of Law, University of Jember, Indonesia, 2023)
Fulfillment of Rural Bank Regulations and Transformation of Village Credit Institutions that are Given Status into Rural Credit Banks. As regulated in Article 2 paragraph (1) which regulates that BPR provisions must be fulfilled by BKD. In reality, not all BKD practices can meet the requirements to become a BPR, because BKD does not have the status of a legal entity, but has a unique work system, namely management that is carried out in a simple and integrated manner. Operational hours are only carried out at certain times and not every day to carry out operational activities. This research uses a normative juridical method with a statutory and conceptual approach. The result of this research is the transition from BKD to LKM based on OJK regulation no. 10/POJK.03/2016 concerning compliance with BKD transition provisions has a significant impact on BKD. This regulation requires BKD to change its legal entity status. The transition of BKD to LKM in the form of PT will provide benefits in terms of legal and institutional responsibilities. As a PT, BKD has the status of a separate legal entity and is clearly regulated in statutory regulations. This ensures that BKD/LKM operates in accordance with applicable regulations and provides safe and reliable financial services to village communities. Conclusion The legal certainty of the deed in changing BKD to LKM has a legal basis which is contained in POJK 10/POJK.03/2016 and Article 4 of the LKM Law, with this legal basis the change in the deed of BKD to LKM has legal certainty and with this legal certainty, MFIs can carry out their activities which have a significant role in society. KEYWORDS: Financial Institutions, Transition, Legal Certainty, Legal Consequences.